Outcomes of various laryngoscopic methods of cordectomy in patients with bilateral abductor vocal fold paralysis: a randomized clinical trial - Sameh M. Zamzam; Hady Salah Eldin AbdelAzim; Aisha Fawzy Abdel Hady; Muhammed Abd Al-lateef Al-Doukany; Ahmed Adel Abdallah (The Egyptian Journal of Otolaryngology)
Abstract Background Bilateral abductor vocal fold paralysis (BAVFP) is a rare yet difficult condition for head and neck surgeons to treat. BAVFP is the most prevalent laryngeal neurological disorder, patients frequently exhibit acute stridor. The current study compares the outcomes of various trans-oral methods of cordectomy in the management of BAVFP. Methods In this prospective randomized clinical trial, 65 patients with BAVFP were randomly divided into three groups, as follows: 23 patients in group A (Ga), “conventional posterior cordectomy with partial arytenoidectomy,” 21 patients in group B (Gb), “laser posterior cordectomy with partial arytenoidectomy,” and 21 patients in group C (Gc) “coblation posterior cordectomy with partial arytenoidectomy.” Results There was no statistically significant difference between the three methods used in this study to manage bilateral vocal fold paralysis. Conclusion Each method had pros and cons that guided the optimal choice of surgeon for each patient. We suggest that coblation has good postoperative outcomes with minimal complications and is a cost-effective method in comparison to the laser. Also, the conventional method could be considered if it was the only available method, and the patient could not be referred to a more equipped center.